Talent Management: Assessment and Prediction of The Efficiency of Work of The Personnel - ODINTSOVA, MARIYA A. (The journal of contemporary issues in business and government, 2021)
Today, talent management is one of the promising areas of work with personnel. Popular Talent Management Systems, which are used both as independent solutions and as subsystems of Enterprise Performance Management. The performance management system used as a basic tool, for example, a balanced scorecard, makes it possible to form key performance indicators for employees based on the strategic goals of the company. Thanks to information systems, HR-managers track the achievement of relevant KPIs, manage the training of employees, conduct their assessment, including professional skills and personal qualities. However, the functionality of the TMS-class information systems on the market does not yet cover all aspects of talent management from a practical point of view. The article presents the functionality of typical Talent Management Systems. The types and tools of talent assessment as important components of talent management are considered. The necessity and practical importance of predicting the effectiveness of key employees of the enterprise made and justified the choice of the most appropriate methods and models of forecasting. The conclusion is made about the possibility and direction of further development of Talent Management Systems. The considered aspects of talent management can be used as a basis for the development of functional requirements for the improvement of TMS software.